Las vacaciones de Mr. Bean - Atkinson, Rowan.; Baldry, Max.; Bendelack, Steve.; Bennett-Jones, Peter.; Bevan, Tim.; Caunes, Emma de, 1976-; Dafoe, Willem.; Driscoll, Robin.; Fellner, Eric.; McBurney, Simon.; McColl, Hamish.; Roden, Karel, 1962- (Universal Studios Home Entertainment, 2007)
Bonus features: Deleted scenes; French Beans; Beans in Cannes; The human Bean.